2021
DOI: 10.3390/ani11113314
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Improves Intestinal Health and Immunity through Modulation of Gut Microbiota in Mice Infected by Pathogenic Escherichia coli O1

Abstract: The effect of emodin on the intestinal mucosal barrier of a mouse E. coli O1-induced diarrhea model was observed. Following successful establishment of a diarrhea model, the mice were treated with drugs for seven days. Intestinal lesions and the shape and the number of goblet cells were assessed via hematoxylin-eosin and periodic-acid-Schiff staining, while changes in inflammatory factors, ultrastructure of the small intestine, expression of MUC-2, and changes in the intestinal microbiota were analyzed via RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In this investigation, LPS-challenge increased Proteobacteria abundance and decreased Bacteroidetes abundance, but ED reversed the adverse changes induced by LPS. Consistent with our findings, Gao et al. (2021) found that ED increased Bacteroidetes abundance while decreasing Proteobacteria abundance in a mice model of diarrhea.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this investigation, LPS-challenge increased Proteobacteria abundance and decreased Bacteroidetes abundance, but ED reversed the adverse changes induced by LPS. Consistent with our findings, Gao et al. (2021) found that ED increased Bacteroidetes abundance while decreasing Proteobacteria abundance in a mice model of diarrhea.…”
Section: Discussionsupporting
confidence: 91%
“…Supplemental ED relieved LPS-induced adverse effects on intestinal morphology of piglets. Similarly, ED was found to reduce pathological damage of intestinal mucosa in septic rats ( Li et al., 2020 ) and E. coli challenged mice ( Gao et al., 2021 ). Plasma D-lactate and DAO are sensitive circulating markers of intestinal permeability ( Arrieta et al., 2006 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Differentiated gut microbiota compositions are often used to study the regulatory function of intestinal flora. Previous studies showed that a variety of food or drug components, such as pectin, 22 , 50 a high-fiber diet, 51 a high-fat diet, 52 emodin, 53 quercetin 54 and various antibiotics, 55 changed the composition of the intestinal flora and affected its function. Artificially induced intestinal flora dysbiosis using antibiotics in healthy mice raised in the same living environment generated large differences in gut microbiota due to the distinct antimicrobial spectrum, which likely produces considerable differences in pathological responses.…”
Section: Discussionmentioning
confidence: 99%
“…The key mechanism of both microbiota is that they are producers of SCFAs, and the effects of SCFAs have been summarized above ( 78 ). Furthermore, Akkermansia participated in the repair of the intestinal barrier through upregulating the expression of ZO-1 and occludin in vivo and in vitro ( 74 ). As a pivotal source of acetic acid production, Lactobacillus was also regarded as a probiotic, and its curative effect was detected in obese subjects with T2DM through an RCT of fecal microbiota transplantation ( 77 ).…”
Section: Multiple Targets Of Natural Polyphenols In Metabolic Disorde...mentioning
confidence: 99%